Effect of five substrates on growth indices of papaya (Carica papaya L.) plants under glasshouse conditions - Gil, Arlette Ivonne; Miranda, Diego (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2011)
In this experiment there were evaluated the effects of five substrates (peat, soil, peat + burned rice husks mixture, sand and the so-called “conventional substrate”) on the ‘Maradol’ papaya and the ‘Tainung-1’ hybrid plant growth, under greenhouse conditions, at the National University of Colombia, in Bogota. Leaf area and dry matter weight were weekly measured, from germination to 56 days after emergence (DAE) period. Leaf area index (LAI), relative growth rate (RGR), crop growth rate (CGR) and net assimilation rate (NAR) were calculated. Peat (Klasmann®), was the most suitable substrate for both materials, because provided the best physical and chemical conditions for both growth and development. Thus, results showed that plants growing on both materials showed preference to peat-moss. The ‘Tainung-1’ hybrid showed a better behavior with respect to ‘Maradol’. Finally, the plants growing on peat showed the highest CGR values with 1.34 g·cm-2·day-1 for ‘Tainung-1’ and 1.20 g·cm-2·day-1 for ‘Maradol’. Furthermore, the supply of rice husks or hen manure affected negatively leaf area and shoot development.